PKM PENGASAPAN IKAN YANG RAMAH LINGKUNGAN UNTUK MENINGKATKAN KUALITAS PRODUK, MANAJEMEN, DAN PEMASARAN DI DESA PENATARSEWU KECAMATAN TANGGULANGIN KABUPATEN SIDOARJO - Daimul Abror; Rasyadan Taufiq Probojati; Susi Ratnawati (Universitas Kadiri, 2022)
PKM partners are SMEs engaged in the smoked fish business, production and marketing having their address in Penatarsewu Village, Tanggulangin District, Sidoarjo Regency. An environmentally friendly smoker is a modern smoker which is expected to be a solution to problems in the production of smoked fish which has not been optimal so far. In the process, smoking using an environmentally friendly smoker is more hygienic than traditional smoking. The results of smoking in an environmentally friendly manner produce better and more delicious colors, aromas, tastes and textures. Problems in the production aspect: (1) The production location is narrow and limited, (2) There are more buyers and product orders, while there is no labor (3) The smoking is still manual, so the smoke pollutes the environment, the smoking time is long (4) The results are uneven , some are too ripe, some are still undercooked, (5) There is no nutrition and expiration test, (5) There is no environmentally friendly smoking device, (6) There is no large capacity storage space (7) Capital. The impact is (1) the order is increasing, the place of production is limited, (2) the need for workers is increasing, recruiting workers requires a large budget. (3) Smoke causes pollution to the community around MSMEs, (4) Manual processing hinders the production process, (5) Products go stale quickly if not put in a cooler, there is no expiration date, difficulties when there are large-scale orders, (6) Water content is still high cause the product does not dry quickly, (7) There is no PIRT and the Ministry of Health permit.Problems in the management aspect: (1) Difficulty in finding permanent employees, because many are not interested, (2) Business processes and business SOPs have not been well documented, (3) Capital constraints for business development with sharia concept, and (4) Do not have an integrated information system ordering, raw materials, production and sales. The impact: (1) Business management is still traditional, controlled by the owner/family, (2) Constraints in processing information related to the stock of materials and products that have been ordered (3) Limited sharia-based business development, (4) Availability of raw materials depends on the season. Problems in marketing aspects Partners do not have adequate display space. As a result, smoked fish are allowed to accumulate, not properly arranged. During the rainy season, demand decreases.The results of the activities that have been carried out: (1) Training, practice, and assistance in making quality Smoked Fish, the same level of maturity, nutrition testing and natural preservation (2) Training, practice, and mentoring of business process management materials and ISO 9001: 2015 regarding quality management standards, (3) Training, practice, and assistance for sharia-based business management (4) Design and layout of new product display rooms, production rooms, product storage rooms, (5) Design of environmentally friendly fumigation machines. Outcome targets: (1) Smoked fish products with the same maturity quality, not easily spoiled and do not smell fishy, (2) Quality management based on ISO 9001:2015, (3) Able to get sharia capital, (4) Design and layout of the display room for smoked fish products (5) New innovations of environmentally friendly smoking machine TTG (6) Publications in the Journal of Community Service (ABDIDAS), (7) Publications in the international journal IJMRA, (8) Articles in mass media/online at www.radarjatim .com, (9) videos of PKM activities uploaded on Youtube, (10) Student Involvement of the MBKM program is equivalent to 6 credits of Entrepreneurship courses [1]